Monitoring and reconstructing past biogeomorphic succession within fluvial corridors using stereophotogrammetry. Issue 10 (7th June 2016) - Vautier, Franck; Corenblit, Dov; Hortobágyi, Borbála; Fafournoux, Laure; Steiger, Johannes
Abstract: Past fluvial biogeomorphic succession dynamics, i.e. reciprocal interactions and adjustments between vegetation growth and fluvial landform construction, were monitored and reconstructed using stereophotogrammetry. The four‐dimensional spatio‐temporal stereophotogrammetric analyses were based on the use of archival analogue and digital aerial photographs. First, we tested the relevance of the technique to produce floodplain digital terrain models (DTMs) and cover height models (CHMs) of the dynamic River Allier, France, and compared the models derived from photogrammetric procedures to field measurements for CHMs and to LiDAR data for DTMs. Automatic photogrammetric procedures tended to create inaccurate digital models with production of outliers, incomplete sectors and areas of confusion especially for analogue stereo‐pairs. Expert correction using stereoscopic viewing improved the vertical accuracy of the digital models, but the vegetation height tended to be underestimated: approximately 0.50 m for vegetation heights less than 10 m, up to 1.50 m for tree heights higher than 25 m. Second, we applied this method to a wooded point bar located on the channelized River Garonne, France. At the scale of the point bar, accurate biogeomorphic maps that show terrain and vegetation height changes in all three spatial dimensions were produced and accurate vegetation growth curves from the early stages of establishment until maturity were extracted. Assuming that a set of conditions is satisfied (e.g. spatial scale of investigation, quality of the photographs), our results show that the photogrammetric method applied in this research can be used operationally to detect and quantify present fluvial biogeomorphic dynamics (i.e. changes of topography and vegetation canopy height) within fluvial corridors of temperate rivers with satisfactory accuracy. Copyright © 2016 John Wiley & Sons, Ltd.